2012
DOI: 10.1371/journal.pone.0039020
|View full text |Cite
|
Sign up to set email alerts
|

Formal Public Health Education and Career Outcomes of Medical School Graduates

Abstract: BackgroundFew data are available evaluating the associations of formal public health education with long-term career choice and professional outcomes among medical school graduates. The objective of this study was to determine if formal public health education via completion of a masters of public health (MPH) degree among US medical school graduates was associated with early and long-term career choice, professional satisfaction, or research productivity.MethodsWe conducted a retrospective cohort study in 110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Its current scope of practice is not with direct patient care. Similar to other countries, work is at local, regional and national levels [4–7], often in policy and leadership positions [8,9], in public institutions, in academia and research [5,10]. Specialists qualify through four-year university-based training progammes accredited by the HPCSA.…”
Section: Introductionmentioning
confidence: 99%
“…Its current scope of practice is not with direct patient care. Similar to other countries, work is at local, regional and national levels [4–7], often in policy and leadership positions [8,9], in public institutions, in academia and research [5,10]. Specialists qualify through four-year university-based training progammes accredited by the HPCSA.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a 2007-2009 cohort study at Tulane University showed, compared to those without an MPH, medical graduates with an MPH were more likely to work in academic or government institutions 10-20 years after graduation. The study also showed that MPH holders were 39.84 times (95% CI 12.13-107.38) more likely to practice public health, as well as conduct public health research and produce scholarly works (25).…”
Section: Comparison With Prior Studiesmentioning
confidence: 80%
“…The Organizational Justice Scale 5 was divided into distributive justice and procedural fairness sections. “Distributive justice”, using a questionnaire prepared by Marshfield, 8 refers to the results obtained by the perception of fairness, including five categories.…”
Section: Methodsmentioning
confidence: 99%
“…Current studies indicate that job burnout occurs frequently in professional practitioners who deal with other persons, such as teachers and health care practitioners. 4 , 5 Therefore, it is important to study job burnout among health care professionals.…”
Section: Introductionmentioning
confidence: 99%